JITA - a social business Bangladesh Ltd: proposal development for acquiring donor funding - Mahin, Kazi Tamanna (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.